Financial incentives in organizations with turquoise management style ("Journal "U". Economy. Management. Finance.", 2023)
The research conducted in this article examines an innovative management style - turquoise. The issues of employee incentives are being studied, namely, how material motivation is organized in such firms. The features of financial incentives in organizations with a turquoise management style.
Keywords: motivation; material incentives; labor incentives; turquoise management style; monetary incentives